METODE PEMBELAJARAN INQURY DALAM MENINGKATKAN KEMAMPUAN MENULIS TEKS PIDATO - Sukanah, Dede; Rahayu, Galih Dani Septiyan (IKIP Siliwangi, 2021)
The ability to write the speech text is one that must be mastered by the classical student in the field of reading, that is, by putting ideas and ideas into written form is not easy. After observations and interviews at the elementary school of the Komplek Ciampel, a number of writing problems have been identified with the factors involved in teachers, students, the media, and the learning models used in learning. The research aims to find out the difference in the ability to write down the text of students' speeches and to describe the inquiry's methods as more effective than the discovery learning model in developing the ability to write speeches on student VI elementary schools of Komplek Ciampel. This kind of research is the inquiry method in the posttest form. So selected the sample of the VIa class experiment group as an experiment class and the VIb class as a control class. The results of this study indicate a significant difference between the experimental class and the control class is seen in the higher average experimental class than the control class.